A Glance at Agrarian Problems in Jambi - Muttaqin, Muhammad Adib; Hasibuan, Yandi; Gaye, Ebrima; Alshaheri, Azzam (Talenta Publisher, 2024)
This study explained at a glance problem agrarian in Jambi with​ use approach study qualitative in a way critical and systematic. Some the sources used, namely experience direct researchers, books, journals, and works scientific-scientific others. Research results show problem agrarianism that occurred in Jambi was ongoing problems​ repetitive between Jambi society with businessman as well as government. Events encroachment land often experienced by the Jambi community and not seldom land seized by the company is the only one owned by the Jambi community for continue desire life. Event repetitive this at least based on several factors, namely quality education Jambi society in particular in understand history and law agrarian tend weak. Reality social participate show distribution power no spread across Jambi and the prevailing tendency have is desire life eternal from power economy and politics so there are no agrarian problems in Jambi Once finished completed in a way comprehensive Because the government doesn't either take action.